Evaluation of Immunogenicity of a Commercially Available Live Attenuated Vaccine for Dogs Containing Canine Distemper Virus and Canine Parvovirus in African Wild Dog (Lycaon pictus pictus). Issue 3 (2018) - Wahldén, Lotta; Emanuelson, Ulf; Møller, Torsten; Wensman, Jonas Johansson
No abstract available